Porcine NK Cells Stimulate Proliferation of Pseudorabies Virus-Experienced CD8+ and CD4+CD8+ T Cells - De Pelsmaeker, Steffi; Devriendt, Bert; De Regge, Nick; Favoreel, Herman W. (Frontiers in Immunology, 2019)
Natural killer (NK) cells belong to the innate immune system and play a central role in the defense against viral infections and cancer development, but also contribute to shaping adaptive immune responses. NK cells are particularly important in the first line defense against herpesviruses, including alphaherpesviruses. In addition to their ability to kill target cells and produce interferon-γ, porcine and human NK cell subsets have been reported to display features associated with professional antigen presenting cells (APC), although it is currently unclear whether NK cells may internalize debris of virus-infected cells and whether this APC-like activity of NK cells may stimulate proliferation of antiviral T cells. Here, using the porcine alphaherpesvirus pseudorabies virus (PRV), we show that vaccination of pigs with a live attenuated PRV vaccine strain triggers expression of MHC class II on porcine NK cells, that porcine NK cells can internalize debris from PRV-infected target cells, and that NK cells can stimulate proliferation of CD8+ and CD4+CD8+ PRV-experienced T cells. These results highlight the potential of targeting these NK cell features in future vaccination strategies.